Collagen and Gelatin Extraction from Manyung Bone Waste as Alternative Halal Raw Materials for Food Production - Kholis Amalia Nofianti; Nia Safitri; Khomsya Ninteen Januar; Diajeng Putri Paramita; Norhayati; Luqmanul Hakim (UIN Sunan Gunung Djati Bandung, 2026)
Collagen and gelatin are widely used in the food and pharmaceutical industries, yet their halal status remains a persistent concern for many products on the market. This study aimed to optimize the extraction and isolation of halal collagen and gelatin from Manyung fish bone waste, an abundant and low-cost Indonesian resource. Collagen was extracted at varying acid concentrations and reaction times, while gelatin was produced under eight treatment conditions varying in acid type, processing temperature, and extraction duration. Collagen and gelatin were characterized by Fourier Transform Infrared Spectroscopy (FTIR). In addition, the resulting gelatin was qualitatively examined using potassium dichromate and trinitrophenol solutions, which are commonly applied in Indonesia’s pharmaceutical industry. The FTIR spectrum of collagen showed absorption peaks corresponding to amide A, amide I, and amide II, whereas amide B and amide III bands were not detected. The highest collagen yield (4.4%) was obtained using 0.75 M acetic acid with a 5-day reaction time. For gelatin, FTIR confirmed the presence of characteristic amide A, amide B, amide I, amide II, and amide III bands. The optimal gelatin extraction was achieved with treatment 8, which involved immersion in 4% HCl, followed by 4% H₃PO₄, and extraction at 80°C for 6 hours, yielding 3.74%. Overall, these findings demonstrate that Manyung fish bone waste is a promising alternative source of halal collagen and gelatin, with potential applications in both food and pharmaceutical manufacturing.